2009
DOI: 10.1158/1535-7163.mct-09-0820
|View full text |Cite
|
Sign up to set email alerts
|

A phase I trial of paclitaxel and trastuzumab in combination with interleukin-12 in patients with HER2/neu-expressing malignancies

Abstract: Our preclinical work showed a dramatic synergy between interleukin-12 (IL-12) and trastuzumab for stimulation of natural killer cell cytokine secretion. We aimed to determine the safety profile of IL-12 when given in combination with trastuzumab and paclitaxel to patients with metastatic HER2-overexpressing cancers. Paclitaxel was given i.v. at 175 mg/m 2 every 3 weeks. Trastuzumab was given on day 1 each week (4 mg/kg initially and 2 mg/kg thereafter) in combination with injections of IL-12 on days 2 and 5 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 29 publications
5
70
1
Order By: Relevance
“…30,31 However, the FDA and Health Canada approvals for trastuzumab (Herceptin r ) treatment include all types of oesophagogastric adenocarcinomas; therefore, strict criteria for ErbB2 assessment in oesophageal adenocarcinomas are of the highest clinical relevance for selecting patients for ErbB2-targeted treatment, which may represent an expensive but promising additional therapeutic option for the advanced stages of this disease. [32][33][34][35][36] In summary, in this study, we found that a significant number of oesophageal adenocarcinomas are positive for ErbB2. The assessment of ErbB2 by immunohistochemistry in combination with in situ hybridisation (bright field double in situ hybridisation or fluorescence in situ hybridisation) reveals highly relevant prognostic information and may also serve as a basis for targeted trastuzumab therapy.…”
Section: Discussionmentioning
confidence: 79%
“…30,31 However, the FDA and Health Canada approvals for trastuzumab (Herceptin r ) treatment include all types of oesophagogastric adenocarcinomas; therefore, strict criteria for ErbB2 assessment in oesophageal adenocarcinomas are of the highest clinical relevance for selecting patients for ErbB2-targeted treatment, which may represent an expensive but promising additional therapeutic option for the advanced stages of this disease. [32][33][34][35][36] In summary, in this study, we found that a significant number of oesophageal adenocarcinomas are positive for ErbB2. The assessment of ErbB2 by immunohistochemistry in combination with in situ hybridisation (bright field double in situ hybridisation or fluorescence in situ hybridisation) reveals highly relevant prognostic information and may also serve as a basis for targeted trastuzumab therapy.…”
Section: Discussionmentioning
confidence: 79%
“…Even in patients with metastatic HER2 þ breast cancer, where the combination of IL-12 with paclitaxel and trastuzumab resulted in a 52% rate of clinical benefit in a phase I trial, the combinatorial strategy was not further pursued. 121 More encouraging results, however, were obtained when treating hematological cancers (Table 1). A phase I dose escalation trial with s.c. delivery of IL-12 twice a week for up to 24 weeks resulted in an overall response rate of 56% in cutaneous T-cell lymphoma patients.…”
Section: Il-12 To Treat Human Cancermentioning
confidence: 98%
“…Also, fibronectin 1 (FN1) and PDGF receptor B (PDGFRB) appeared repeatedly together specifically in DCIS, along with COL1A2, IL-12/IL-12 receptor/TYK2/JAK2/SPHK2, ESR1, and KRT14. Phase I clinical trials have shown that the clinical effect of trastuzumab (Herceptin) is potentiated by the coadministration of IL-12 to patients with HER2-overexpressing tumors, and this effect is mediated by the stimulation of IFN-γ production in the NK cells (19). (Fig.…”
Section: Paradigm Analysis Of Normal Breast Tissue With High and Lowmentioning
confidence: 99%